Blasphemy against the Holy Spirit Rejecting the Sign of the Covenant - Callaham, Scott N. (2023)
One of the notorious interpretive cruces within the Synoptic Gospels concerns blasphemy against the Holy Spirit. According to Jesus, this sin stands apart from and above all others as an unforgivable offense. Attempts to explain the internal logic of these sayings and their place within Jesus’s teaching have left New Testament scholarship at an impasse. The present study advances a fresh perspective: that blasphemy against the Holy Spirit means radically rejecting the sign of the New Covenant, hence the offender experiences the covenant sanction of irrevocably being “cut off.”